1986
DOI: 10.1093/jac/17.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral ciprofloxacin, 100 mg single dose, in volunteers and elderly patients

Abstract: The pharmacokinetics of ciprofloxacin following a single 100 mg oral dose were evaluated in elderly patients (mean age 74 years), laboratory staff (30-40 years) and students (less than 20 years). There were no significant differences in serum Tmax (1.2-1.3 h) or in overall serum elimination half-life (3.7-4.0 h) but Cmax in elderly patients was more than double that in young volunteers (P less than 0.005). The serum AUC value was greater both in fasting students (1.4 mg/h/l) compared with the same subjects aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
21
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 0 publications
5
21
0
Order By: Relevance
“…As seen in previous studies (1,8), the plasma ciprofloxacin concentrations in our study were higher in elderly subjects. Increases in the C max and AUC and an increase in the half-life were observed for the elderly subjects compared with the young.…”
supporting
confidence: 89%
“…As seen in previous studies (1,8), the plasma ciprofloxacin concentrations in our study were higher in elderly subjects. Increases in the C max and AUC and an increase in the half-life were observed for the elderly subjects compared with the young.…”
supporting
confidence: 89%
“…No significant differences were noted between the first dose and steady-state pharmacokinetic parameters, with the exception of an increase in the apparent volume of distribution. The results were consistent with previous studies in healthy and mildly ill elderly subjects undergoing assessment after single doses of oral ciprofloxacin in that the maximum concentration of drug in serum (Cmax) and area under the concentration-time curve (AUC) were increased compared with those of young volunteers receiving the same doses (2,3,5,9,11,15).These studies suggest that the pharmacokinetics of ciprofloxacin are altered in elderly subjects. However, comparative intravenous and oral ciprofloxacin pharmacokinetic parameters during maintenance dose therapy in the elderly have not been evaluated.…”
supporting
confidence: 90%
“…Few investigators have compared the disposition of ciprofloxacin in elderly subjects and young volunteers. Ball et al (2) reported significant increases in the peak ciprofloxacin concentration in serum and area under the serum-concentration-versus-time curve in elderly patients with mild urinary tract infections compared with young volunteers after a single 100-mg oral dose. In both groups, the mean terminal elimination half-lives were almost identical.…”
mentioning
confidence: 99%
“…This increase in concentration may be of therapeutic use but may also contribute to intolerance reactions, especially in patients with renal or hepatic insufficiency. In this context also, the higher ciprofloxacin concentrations in serum in elderly patients, which had been reported by Ball et al (2), should be considered.…”
Section: Discussionmentioning
confidence: 71%
“…The pharmacokinetic characteristics of ciprofloxacin, with a terminal half-life of 3.5 to 4 h, allows twice-daily administration by the parenteral or oral route (2,29).…”
mentioning
confidence: 99%